Identifying and Mapping Human Capital Risk in the State-Owned Enterprises Organization: Evidence from PT Pupuk Indonesia - Margaretha Banowati Talim; Franciskus Antonius Alijoyo (Jurnal Ilmiah Akuntansi Kesatuan, 2026)
The study of human capital risk remains underexplored despite its critical role in ensuring organizational success. This research aims to examine the interrelationships among enterprise risk management maturity, risk culture, human capital development, employee competencies, and leadership in mitigating human capital risk. This research employs a quantitative explanatory approach, using questionnaires as the primary data collection method to analyze the relationships among the studied variables. The findings reveal that higher enterprise risk management maturity significantly reduces human capital risk by enabling a more proactive and systematic approach to risk identification and mitigation. Leadership capability emerges as a crucial factor, alongside structured and targeted human capital development programs that enhance employee competencies. A key contribution of this study is the development of a human capital risk heat and mitigation matrix, which provides a practical framework for managing human capital-related risks. This framework is particularly relevant for State-Owned Enterprises (SOEs) in emerging markets that face complex and dynamic competitive environments. By integrating enterprise risk management maturity principles with human capital strategies, organizations can strengthen resilience, improve agility, and sustain competitiveness in a VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) environment.